2011
DOI: 10.1186/1476-7120-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous leiomyomatosis of the uterus with extension to the right heart

Abstract: A 42-year-old woman admitted with debilitation and engorgement both lower extremities. Transthoracic two-dimensional echocardiography, abdominal ultrasound and computerized tomography revealed a lobulated pelvic mass, a mass within right internal iliac vein, both common iliac vein, as well as the inferior vena cava, extending into the right atrium. In addition, echocardiography and abdominal ultrasound showed the tumor of right atrium and inferior vena cave has no stalk and has well-demarcated borders with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…In total, ∼90% of reported cases have occurred in parous females and 10% of patients have presented with a history of previous pelvic surgery and hysterectomy (4). It has been suggested that an incomplete hysterectomy may promote the proliferation of IVL (5), or alternatively, that IVL may originate in the smooth muscle cells of the vessel wall (6). The present study patient had a normal pregnancy and delivered via cesarean section four years earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, ∼90% of reported cases have occurred in parous females and 10% of patients have presented with a history of previous pelvic surgery and hysterectomy (4). It has been suggested that an incomplete hysterectomy may promote the proliferation of IVL (5), or alternatively, that IVL may originate in the smooth muscle cells of the vessel wall (6). The present study patient had a normal pregnancy and delivered via cesarean section four years earlier.…”
Section: Discussionmentioning
confidence: 99%
“…It is most commonly observed in middle-aged females (5) and in conjunction with leiomyoma of the uterus or an ovarian tumor (8). Two-thirds of patients exhibit diffuse symptoms, including pelvic discomfort or abdominal pain; however, IVL may also be diagnosed accidentally during abdominal US, unrelated surgeries or at autopsy (9).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous leiomyomatosis is a rare histologically benign intravascular tumor of uterine origin, and the most commonly affected patients are premenopausal and multiparous females aged 20 to 70 years, with a mean age of 45 (8). The clinical course of the disease is variable and is determined by the position and scale of the neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…36 Benign smooth muscle fibers invade the venous channels of the pelvis and, even though they grow slowly, they might grow into the vena cava and right heart and cause these unusual symptoms. Surgical intervention with primary excision and follow-up antiestrogen therapy for prevention is recommended to treat these cases.…”
Section: Cardiac Symptom and Atypical Symptoms Secondary To Vascular mentioning
confidence: 98%